Identification of a diverse synthetic abietane diterpenoid library for anticancer activity. Issue 3 (1st February 2017) - Xu, Hongtao; Liu, Lili; Fan, Xiaoting; Zhang, Guanjun; Li, Yuanchao; Jiang, Biao
Graphical abstract: Abstract: A diverse natural-product-like synthetic abietane diterpenoid library contains about 56 compounds were obtained, and evaluated for their potential in vitro cytotoxic or antitumor activity against A549, PC-3 and SKOV-3 tumor cell lines by SRB assay. Treatment of A549 cells with the most potent compound ketone19 showed induction of apoptosis, as revealed by JC-1 mitochondrial membrane potential staining, TUNNEL assay, western blotting analysis and flow cytometry assay.